PJMHS 2022
DOI: 10.53350/pjmhs22166310
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Marital Screening: Thalassemia Trait and Iron Deficiency Anemia in Rahim Yar Khan, Pakistan

Abstract: Objective: β- thalassemia Minor (BTM) and Iron Deficiency Anemia (IDA) are the main causes of microcytic hypochromic anemias currently in Asian subcontinent. Healthcare facilities in Pakistan have to encounter massive number of patients with anemias every day, where we need to distinguish between (IDA) and (BTM). A number of discrimination indices have been suggested for rapid differentiation of these entities over parameters achieved from automated blood-count analyzers. Objective. To determine the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Other than above a recent study from an area of south Punjab demonstrated thalassemia trait among 3.3% males and 2.2% females is also alarming and considering the importance of pre-marital status. 16 Another study from Lahore also demonstrated the significance of pre-marital screening and presented 7.5% of thalassemia trait using hemoglobin electrophoresis among women.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other than above a recent study from an area of south Punjab demonstrated thalassemia trait among 3.3% males and 2.2% females is also alarming and considering the importance of pre-marital status. 16 Another study from Lahore also demonstrated the significance of pre-marital screening and presented 7.5% of thalassemia trait using hemoglobin electrophoresis among women.…”
Section: Discussionmentioning
confidence: 96%
“…Pregnant women having multiple gestations confirmed on ultrasonography, pre-diagnosed cases of thalassemia or Sickle cell anaemia and having any known chronic medical disorder like Chronic Kidney Disease, Acid Peptic Disease or Piles etc. were excluded from this study 15,16,17 . Data Collection Procedure: A total of 310 pregnant women were included.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] Thrombocytopenia (TCP) is the second most common hematological change in pregnant women and a notable source of maternal and neonatal morbidity and mortality. [ 2 , 3 ] The global prevalence of TCP among pregnant women is 8.4% and around one-tenth of pregnant women are suffered worldwide. [ 4 ] Studies reported that a reduction in platelet count during pregnancy resulted in levels about 10% lower than the pre-pregnancy level at term.…”
Section: Introductionmentioning
confidence: 99%